Implementasi model cakap berbasis project based learning untuk meningkatkan keterampilan berbicara berbantuan media visual: Indonesian - Hayati, Rasona Pooza; Suriansyah, Ahmad; Purwanti, Ratna; Agusta, Akhmad Riandy (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The problem of low speaking skills in grade IV SDN Sidorejo 2 can be seen through indicators of speaking skills. Based on observation activities in learning have not provided space to develop speaking skills, resulting in low student activity, skills, and learning outcomes. Efforts to overcome these problems are carried out through the implementation of the innovative model CAKAP learning based on Project Based Learning. This study aims to determine the influence of the CAKAP model in improving the quality of learning through teacher activities, student activities, speaking skills, and learning outcomes. This study used a type of classroom action research. The results showed increased teacher activity, student activity, speaking skills, and student learning outcomes through four action cycles and achieved the established success indicators. Based on the results, CAKAP model can improve the quality of learning by increasing teacher activity, student activity, speaking skills, and student learning outcomes.